2018
DOI: 10.1002/app.46389
|View full text |Cite
|
Sign up to set email alerts
|

Curing reaction mechanism and heat resistance properties of hexa‐(4‐carboxyl‐phenoxy)‐cyclotriphosphazene/bisphenol A aniline benzoxazine blends

Abstract: A blend system of hexa‐(4‐carboxyl‐phenoxy)‐cyclotriphosphazene (HCPCP) and bisphenol A aniline benzoxazine (BA‐a) was prepared, and its curing reaction mechanism and heat resistance properties were studied. The curing reaction mechanism of the blend was explored by differential scanning calorimetry, Fourier transform infrared spectroscopy, and modeling software using model compounds Ar‐COOH and hexachlorocyclotriphosphazene (HCCP). The heat resistance properties of the cured blends were studied by thermogravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…It has been reported that organic acids catalyze benzoxazine polymerization [ 17 ]. Most studies present the influence of acid/acidic catalysts as a function of concentration [ 11 , 16 , 17 , 32 , 33 , 34 , 35 ]. In this regard, Figure 3 a presents a similar study for the two cinnamic catalysts investigated in this work, where higher acid concentrations induce greater lowering of T p .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that organic acids catalyze benzoxazine polymerization [ 17 ]. Most studies present the influence of acid/acidic catalysts as a function of concentration [ 11 , 16 , 17 , 32 , 33 , 34 , 35 ]. In this regard, Figure 3 a presents a similar study for the two cinnamic catalysts investigated in this work, where higher acid concentrations induce greater lowering of T p .…”
Section: Resultsmentioning
confidence: 99%
“…1,3,6,8-Tetrakis­( p -benzoic acid) pyrene (H 4 TBAPy) , and hexa-(4-carboxyl-phenoxy)-cyclotriphosphazene (HCPCP) were synthesized according to previous literature. The synthetic process of H 4 TBAPy and ligand HCPCP is shown in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…A number of effective flame-retarded functional epoxy resins, amine curing agents and benzoxazines with a phosphazene core have been proposed [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Carboxyl-containing epoxyphosphazenes and their use as a catalyst for the polymerization of benzoxazines have also been reported [ 22 ].…”
Section: Introductionmentioning
confidence: 99%